Respuesta :
m=−2n+3;2m−3n=6
Solve m=−2n+3 for m
Substitute (−2n+3) for m in 2m−3n=6
2m−3n=6
2(−2n+3)−3n=6
−7n+6=6(Simplify)
−7n+6+−6=6+−6(Add -6)
−7n=0
−7n / −7=0 / −7(Divide by -7)
n=0
Substitute (0) for n in m=−2n+3:
m=−2n+3
m=(−2)(0)+3
m=3(Simplify)
m=3 and n=0
So it is (3,0)
Solve m=−2n+3 for m
Substitute (−2n+3) for m in 2m−3n=6
2m−3n=6
2(−2n+3)−3n=6
−7n+6=6(Simplify)
−7n+6+−6=6+−6(Add -6)
−7n=0
−7n / −7=0 / −7(Divide by -7)
n=0
Substitute (0) for n in m=−2n+3:
m=−2n+3
m=(−2)(0)+3
m=3(Simplify)
m=3 and n=0
So it is (3,0)